A responsabilidade civil objetiva como mecanismo de repersonalização do direito civil: uma análise do artigo 927, parágrafo único, do Código Civil - DUARTE, Bruno Ferreira Montenegro (Universidade Federal do Pará, 2015)
This paper examine in depth the Office of liability under the prism of the New Civil Code. At first look at the constitution of civil law as axiological basis of the current liability. In a second review the Office of liability objective is addressing their origin, their foundation and their theories. Finally it presents the theory of risk in the Brazilian ranking civil identifying their origin, their assumptions, their concepts, and intense approach to Article 927 of the Civil Code. It is the real meaning of the theory of risk and its application in the Brazilian legal system as objective of justice.